Development of a cELISA for effective detection of the antibody against H7 subtype of avian influenza virus - Cong-cong WANG; Si-wen WANG; Ying ZHANG; Jian-zhong SHI; Xin YIN; Cheng-jun LI; Xiu-rong WANG (Journal of Integrative Agriculture, 2022)
H7 avian influenza viruses (AIVs) normally circulated among birds before. From 1996 to 2012, human infections with H7 AIVs (H7N2, H7N3, and H7N7) were reported in Canada, Italy, Mexico, the Netherlands, the United Kingdom and the USA. Until March 2013, human infections with H7N9 AIVs were reported in China. Since then, H7N9 AIVs have continued to circulate in both humans and birds. Therefore, the detection of antibodies against the H7 subtype of AIVs has become an important topic. In this study, a competitive enzyme-linked immunosorbent assay (cELISA) method for the detection of antibody against H7 AIVs was established. The optimal concentration of antigen coating was 5 μg mL−1, serum dilution was 1/10, and enzyme-labeled antibody was 1/3 000. To determine the cut-off value of cELISA, percent inhibition (PI) was determined by using receiver operating characteristic (ROC) curve analysis in 178 AIVs negative samples and 368 AIVs positive serum samples (n=546). When PI was set at 40%, the specificity and sensitivity of cELISA were 99.4 and 98.9%, respectively. This method could detect the antibodies against H7Nx (N1–N4, N7–N9) AIVs, and showed no reaction with AIVs of H1–H6 and H8–H15 subtypes or common avian viruses such as Newcastle disease virus (NDV), Infectious bronchitis virus (IBV) and Infectious bursal disease virus (IBDV), exhibiting good specificity. This method showed a coincidence rate of 98.56% with hemagglutinin inhibition (HI) test. And the repeatability experiment revealed that the coefficients of variation (CV) of intra- and inter-batch repetition were all less than 12%. The data indicated that the cELISA antibody-detection method established in this study provided a simple and accurate technical support for the detection of a large number of antibody samples of H7-AIV.